Theoretical investigation study based on PM3MM and ONIOM2 calculations of β-Cyclodextrin complexes with diphenylamine - Abdelaziz Bouhadiba; Leila Nouar; Sakina Haiahem; Imene Djilani; Fatiha Madi; DjamelEddine Khatmi (My University, 2012)
The inclusion complex of b-cyclodextrin (b-CD) and diphenylamine (DPA) was investigated by using PM3MM, DFT, HF and ONIOM2 methods. The most stable structure was obtained at the optimum position and angle. The results indicate that the inclusion complex formed by DPA entering into the cavity of b-CD from its wide side (the secondary hydroxyl group side) is more stable than that formed by DPA entering into the cavity of b-CD from its narrow side (the primary hydroxyl group side). The structures show the presence of several intermolecular hydrogen bond interactions that were studied on the basis of natural bonding orbital (NBO) analysis, employed to quantify the donor–acceptor interactions between diphenylamine and b-CD. A study of these complexes in solution was carried out using the CPCM model to examine the influence of solvation on the stability of the diphenylamine b-CD complex.